Two giant planets orbiting the K giant star η Cet - Trifonov, Trifon; Reffert, Sabine; Quirrenbach, Andreas (Proceedings of the International Astronomical Union, 2013)
We present evidence of a new planetary system around the K giant η Cet (HIP 5364, HD 6805, HR 334), based on 124 high-precision optical and infrared radial velocity data, taken at Lick Observatory (Hamilton) and at VLT (CRIRES). The best dynamical fit to the data is consistent with two massive planets (m1sini≈2.6MJup, m2sini≈3.3MJup) and with periods of P1≈407 days, P2≈740 days. To test the η Cet system's stability we perform ~ 10,000 dynamical investigations with maximum time spans of 108 years. We find that in case of moderate eccentricities, the planets can be effectively trapped in an anti-aligned stable 2:1 mean motion resonance (MMR), very close to the separatrix. A larger non-resonant stable region exists in low-eccentricity parameter space, although less probable than the 2:1 MMR region.